Morphological Changes in the Trabecular Meshwork in Eyes with Primary Open Angle Glaucoma - Daud, Fatima (International Journal of Pathology, 2023)
Introduction: Primary open angle glaucoma is a progressive optic neuropathy. It is a leading cause of blindness around the world. Exact etiology is not known although a number of risk factors identified. Glaucoma prevention and cure remains an enormous challenge and for that elaboration of pathogenesis may be helpful.Objective: To determine the morphological changes in the trabecular meshwork in eyes with primary open angle glaucoma.Materials and Methods: A total of 75 trabeculectomy specimens were obtained from Primary open angle glaucoma patients. The tissues were prepared for light microscopy and stained with haematoxylin and eosin. The lamellar thickness and inter-trabecular spaces were measured in micrometer. These numbers were compared with age matched controls. The data was analyzed using SPSS version 21. Student’s t-test was used to compare the obtained values with controls.Results: There was a statistically significant increase in the lamellar thickness (P value = 0.001). The normal trabecular thickness (4.7 µm) was compared with the mean value of trabecular thickness of the samples (10.35 µm). A significant reduction in the inter-trabecular spaces was observed (P value = 0.001) when compared to the values of age matched controls. (Normal inter-trabecular spaces = 25 µm, reduction in spaces = 11.78 µm).Conclusion: This study confirmed and highlighted the histo-pathological changes occurring in the trabecular meshwork of Primary open angle glaucoma. The destructive changes obliterate the passages of delicate trabecular network that may lead to high aqueous resistance and a consequent rise in the IOP.